PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 008 BUKIT KAYU KAPUR - Witri, Gustimal Witri; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of the problem in this research is the teacher doesn’t apply yet or use the learning model well in mathematic leraning process.The teacher is just explain the material without asking the student to find mathematic concept,and do not mathematic as real  activity. Hence it is needed to do learning improvement by applying direct learning.Direct learning model is one of the teaching  approaches which is specifically desaigned to facilatate the student learning process which is accordance with prosedural knowledge in well structured that can be taught in phase activity pattern,step by step.This research is in form of classroom action research ( CAR ).The aim of thiss reseach is to improve the student learning result at grade IV of elementary school 008 Bukit Kayu Kapur.The formulation of the reseach is, “ Does the application of the direct leraning can improve mathematic leraning result of the students at grade IV in elementary school Bukit Kayu Kapur ? This research perform 2 cycle.at first cycle and fiest meeting,the average teacher activity is 55 % enough category.at first cycle second meeting increased become 65 % good category.at second cycle first meeting teacher activity increased become 80 % good category,and last meeting teacher activity increased again become 90 % very good category.The first meeting at first cycle the student activiy is 50 % no so good category,at first cycle second meeting increased become 60 % enough category.At second cycle first meeting the student activity become 75 % good category,and last meeting increased become 85 % very good category.     Keyword : Direct Learning Model,Mathematic Learning Result